MUHAMMAD ABDUH AS A FIGURE IN THE AL-ASHAR EDUCATION REVOLUTION IN SHAPING THE FACE OF ISLAMIC EDUCATION IN INDONESIA - Sari, Ana Kurnia; Amin, Khoirul (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This article contains a description of the thought figure of the Islamic Ulama Muhammad Abduh using a library research approach with a qualitative descriptive research type with data sources coming from books, related articles, scientific journals related to the thoughts of the Islamic Ulama Muhammad Abduh Abduh. Muhammad Abduh was a scholar and reformer of Islamic education who came from Egypt. With his moderate views and efforts in combining Islamic values with modern educational thinking. Education is the main foundation in building a better society. Muhammad Abduh's support for education that prioritizes balance between religious and world knowledge. For him, religious education plays an important role in shaping individual character and morals, while general education makes individuals adapt to the social and scientific changes that occur. Abduh believes that education is the key to social change, emphasizing the importance of societal progress through education. He also highlighted the balance between religious knowledge and world knowledge and promoted inclusive education that was accessible to all. The importance of critical thinking and freedom of opinion in education is also recognized by Abduh, with the belief that individuals must think independently. Even though his thinking originates from the 19th century, his ideas and principles are still relevant in the context of modern education. Through Abduh's thinking, the importance of education that is holistic, inclusive, and oriented towards individual development morally, intellectually, and socially is recognized. His thoughts can be a source of inspiration in designing an education system that suits the needs of our time.